Evaluation of the link between economic growth and foreign direct investment inflows of sri lanka - Gunarathne, G.S.P. (University of Jaffna, 2018)
Foreign Direct Investment (FDI) inflow is considered as an influential factor ofthe economy in developing nations. The major objective ofthe study is to assessthe relationship between FDI and economic growth in Sri Lanka, this study employeddescriptive analysis, correlation and regression analysis by using data from 1977 to 2016. The findings of the study indicatethe relationship between FDI andeconomic growth rose strongly after the beginning of the 21st century.Since then, there is a strong positive relationship between FDI and economic growth. In addition, the regression analysis indicates that the existence of the positive impact of FDI on economic growth in Sri Lanka.As a summary of the conclusion, there is a positive contribution of foreign direct investmenton economic growth in Sri Lanka. Hence, it is more important to take policy actions to enhance the FDI inflows into Sri Lanka since it gives a positive relationship and positive impact on the economic growth.
Keywords: Descriptive statistics; Economic growth; Foreign direct investment; Gross domestic product; Regression analysis